Digital System Model for Curriculum Management Base on National Educational Standards in Thai Supply Chain - Artaphon Chansamut (ExcelingTech, 2022)
The research was conducted to develop and to evaluate digital system model for curriculum management base on national educational standards in Thai supply chain. A samples group in the research study consisted of ten purposively selected experts consisted of five experts on supply chain management, five experts on digital, Data were analysed by arithmetic mean and standard deviation. The paper findings pattern seven elements namely main components, Suppliers , Manufacture , customers, consumers, satisfaction, feedback . The assessment digital system model for curriculum management base on national educational standards in Thai supply chain using Black-Box technique and The results from experts agreement digital system model for curriculum management base on national educational standards in Thai supply chain was a high level and can be applie in support the tasks.